Peretasan Database UIN Sultan Maulana Hasanudin Banten Berdasarkan Undang Undang Informasi dan Transaksi Elektronik - Daniel Ronaldo Gultom (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The advancement of technology in digital era is growing fastly, However hacking criminal act is growing happened. Hacking case observed by researcher Â is Maulana Hasanudin Banten Moslem Â State University database, researcher on this research use framework of thinking as follows: Law enforcement theory and sentencing law theory. In compiling the identification on this research, First, how law enforcement on hacking Maulana Hasanudin Banten Moslem State University database perpetrator based on Law of Information, Transaction, and Electronics ? Second, how law sentencing on hacking Maulana Hasanudin Banten Moslem State University database perpetrator based on Law of Information, Transaction, and Electronics ? This research use juridical normative methods and empirical normative methods. First observation result Â in enforcement law on perpetrator database is any difficulty to determine criminal law act location and to search lost data caused by hacking act. Second, sentencing on hacking database perpetrator, sentencing on hacking perpetrator is very enthereal and not include minimum sanction in Information, Transaction and Electronics law. So therefore it is necessary must increase law enforcer ability in this case law enforcement on hacking criminal act and must include minimum sanction in law, so that to notice justice people aspect.